Sickle form anemia and the risk of atherosclerosis: the role of treatment (Research, Society and Development, 2021)
Objective: To clarify factors related to sickle cell anemia and the importance of its treatment. Methodology: This is a study of a literary review based on articles that provide information on the topic addressed. In this study, it was carried out through articles in the following electronic databases SciELO (Scientific Electronic Library Online), and Ministry of Health of Brazil, VHL (Virtual Health Library Portal), Revista Update Saúde and others. The selected descriptors were: sickle cell anemia, hemogobinopathy, hemoglobin S, atherosclerosis, diagnosis. The inclusion criteria for the selection of required articles are: articles published in 2016 to date, available and in any language. Exclusion criteria are: old ones whose themes do not match the research objective and duplicate articles in the database. Result: The articles used were published between 2016 and 2020. The articles highlighted sickle cell anemia, specifically the role of treatment for it. It was pointed out in this article, in addition to general information about sickle cell disease, some topics are addressed about the infections most frequently observed in patients with sickle cell anemia, as well as drug prophylaxis and available immunizations. Conclusion: This study was developed as a bibliographic review of theories described regarding sickle cell anemia or the behavior of hemoglobins in the human body. Thus, this study provided us with greater knowledge about sickle cell anemia, describing the implications of sickle cell anemia in people's lives, as it manifests itself. Among general lines, it was possible to see that sickle cell anemia has great relevance from a scientific point of view. Opening paths and new study hypotheses for sickle cell anemia is one of the great challenges for treating the sick, who need the help of health professionals to preserve their perspective on life and social well-being.